Knowledge of Food Label Among Master’s Students of Home Science in Kathmandu: A Cross-Sectional Study - Srijana Baidhya (Journal of Healthcare and Biomedical Science, 2024)
The part of food labels that states the amount of nutrients is called nutrition labeling. This comprises a list of components, a nutrition information table, health endorsement logos and nutritional content claims on product labels. Food labeling is an essential part of any product. As a food producer, it is not only legally required but also empowers customers to make informed food purchases and ensures the safe storage and use of their purchases. Students in food and nutrition should be knowledgeable in the topics of label reading, healthy eating, and how to use food labels as future nutritionists. With this sound understanding, they will be able to counsel their future patients on the proper use of food labels and, as a result, become change agents in the community. It can also help people live healthier lives if food labels are used appropriately. This study aimed to evaluate students’ understanding of food labels in home science. Using a descriptive cross-sectional approach, data were collected through purposive sampling. The findings indicated that among the 118 participants, the majority (98%) were aware of the food labels, although only about half could interpret all the information on them. The study suggests that although most students recognize food labels, they may lack a comprehensive understanding of the details provided. This underscores the importance of public awareness campaigns and educational programs to improve consumer knowledge and the effective use of food label information.